Parathyroid function and calcium concentration in serum of dexamethasone treated rabbits - K., Mashi S.; K., Al-Ar’rak J. (The Iraqi Journal of Veterinary Medicine, 2000)
This experiment was carried out to determine structural functional changes which could be caused due to uses of dexamethasone at daily therapeutic doses in rabbits for a reasonable period. Ten adult male rabbits were randomly divided into two equal groups control and treatment. Animals of the treatment group were intramuscularly injected with dexamethasone sod. citrate (0.06 mg/100g.B.W.) for 14 days. Animals of control group received the same dose of normal physiological saline solution blood samples were collected every other day until 48 hours after the last injection serum was isolated for measurement of calcium concentrations. At the end of the experiment tissue samples from the parathyroid glands were isolate to prepare histological stained sections . Dexamethasone did not cause significant changes in serum concentration of calcium of treated group compared with its concentrations in control group. Light microscopic examination of hematoxylin eosion stained sections of parathyroid gland showed enlargement and increase in number of light chief cells indicating increased secretory activity due to dexamethasone injection. The increased of parathyroid gland activity explain the maintenance of total calcium level within the normal range in spite of the expected hypocalcemia due to dexamethasone administration.